Knowledge Management Impact on Corporate Entrepreneurship in Malaysia - Ansari, Payam (2009)
This research is the first study about corporate entrepreneurship in the context of Malaysia, and with respect to the freshness of knowledge management issues in this developing country, the results and findings of this research would hopefully help other researchers, managers and decision makers to have better and more clear image of corporate entrepreneurship and knowledge management for their future initiatives and endeavors.